2007
DOI: 10.1063/1.2783891
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of Ar∕H2∕CH4 arc jet discharge chemical vapor deposition reactors II: Modeling of the spatial dependence of expanded plasma parameters and species number densities

Abstract: Articles you may be interested inStrange hardness characteristic of hydrogenated diamond-like carbon thin film by plasma enhanced chemical vapor deposition process Appl. Phys. Lett. 102, 011917 (2013); 10.1063/1.4775372Simulations of chemical vapor deposition diamond film growth using a kinetic Monte Carlo model and twodimensional models of microwave plasma and hot filament chemical vapor deposition reactors Synthesis of tin-incorporated nanocomposite diamond like carbon films by plasma enhanced chemical vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…We have extended our previous experimental/modeling studies of H 2 -rich C/H/Ar plasmas (e.g. 4.4%CH 4 /88.6%H 2 / 7%Ar, F total ¼ 565 sccm, p ¼ 150 Torr, P ¼ 1.5 kW) such as are used for growth of MCD films [22][23][24][25] to explore the consequences of major variations in the input H 2 /Ar ratio -from H 2 /Ar mole fraction ratios of > 10:1 as used for MCD growth, through ratios $1:6 (e.g., 0.5%CH 4 /14.7%H 2 / 84.8%Ar, F total ¼ 525 sccm, p ¼ 150 Torr, P ¼ 1.0 kW, the "base" conditions used in most of the present work) typical of those used for NCD growth, and extending to an H 2 /Ar ratio of $1:99 (e.g., 0.5%CH 4 /1%H 2 /98.5%Ar, F total ¼ 525 sccm, p ¼ 150 Torr, P ¼ 0.5 kW) as used for growth of UNCD material. As before, absolute column densities of C 2 (a) and CH(X) radicals and of H(n ¼ 2) atoms have been determined by CRDS, as functions of z and of process conditions [X 0 (H 2 ), X 0 (CH 4 ), X 0 (Ar), p, and P].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have extended our previous experimental/modeling studies of H 2 -rich C/H/Ar plasmas (e.g. 4.4%CH 4 /88.6%H 2 / 7%Ar, F total ¼ 565 sccm, p ¼ 150 Torr, P ¼ 1.5 kW) such as are used for growth of MCD films [22][23][24][25] to explore the consequences of major variations in the input H 2 /Ar ratio -from H 2 /Ar mole fraction ratios of > 10:1 as used for MCD growth, through ratios $1:6 (e.g., 0.5%CH 4 /14.7%H 2 / 84.8%Ar, F total ¼ 525 sccm, p ¼ 150 Torr, P ¼ 1.0 kW, the "base" conditions used in most of the present work) typical of those used for NCD growth, and extending to an H 2 /Ar ratio of $1:99 (e.g., 0.5%CH 4 /1%H 2 /98.5%Ar, F total ¼ 525 sccm, p ¼ 150 Torr, P ¼ 0.5 kW) as used for growth of UNCD material. As before, absolute column densities of C 2 (a) and CH(X) radicals and of H(n ¼ 2) atoms have been determined by CRDS, as functions of z and of process conditions [X 0 (H 2 ), X 0 (CH 4 ), X 0 (Ar), p, and P].…”
Section: Discussionmentioning
confidence: 98%
“…Such data can be obtained, however, by judicious intercomparison between experimental measurement and high level reactor modeling -as illustrated in our previous diagnoses of the gas phase environment in a dc arc jet reactor, 21,22 and in MW activated C/H, 23 B/H, 24 and B/C/H (Ref. 25) plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies reported over the past two decades have provided progressively greater understanding and allowed optimization of diamond deposition processes in relatively simple hot filament CVD reactors [25,[80][81][82][83][84][85], in dc arc jet reactors [86] and in MPCVD reactors [53,65,[87][88][89][90][91][92][93][94][95][96][97]. The latter environment is considerably more challenging; many complex and interrelated phenomena require careful consideration in order to achieve an adequate simulation of the diamond deposition processes occurring in an MW PECVD reactor.…”
Section: Plasma Modelingmentioning
confidence: 99%
“…Monitoring CH provides an insight into the reaction mechanism. CH radicals and C atoms contribute to the experimentally observed high and nonuniform diamond growth rates in the highpower Bristol reactor [7]. The level of CH concentration agreement between the model prediction and the experimental measurement can be used to test model predictions of hydrocarbon chemistry [8].…”
mentioning
confidence: 95%